A case study of Sekolah Menengah Kebangsaan Jengka Pusat 2: the impact of learning style on academic performance among school students / Norlily Suraya Mohd Zin and Juliyana Long - Mohd Zin, Norlily Suraya; Long, Juliyana (2013)
The present study investigated the impact of learning style towards academic performance of school students of Sekolah Menengah Kebangsaan Jengka Pusat 2, Jengka. The number of As attained in PMR was calculated and analyzed for each student and used as a measure of academic performance. This descriptive study collected the data by distributing the questionnaires to 40 students that were randomly selected as sample of this study. The instrument used was adopted from Kolb Learing Style Inventory. The data was collected by distributing survey questionnaires to 40 students and the question were analyzed by using Statistical Package in the Social Sciences Software (SPSS) Version 20. In this study, only one school in Jengka was selected to represent the population of rural area. The result showed that Diverging (watching and feeling) is the learning style that most contribute to the academic achievement of respondent, followed by Converging (thinking and doing), Accommodating (feeling and doing), and Assimilating (watching and thinking) learning style. The school management and students themselves can use these findings in embracing the knowledge about the practices that can be taken into consideration for future undertakings. Other than that, the study also provided some recommendations that highly encouraged to be implemented for future use of other researchers.